2021
DOI: 10.3390/jof7060404
|View full text |Cite
|
Sign up to set email alerts
|

Periprosthetic Fungal Infections in Severe Endoprosthetic Infections of the Hip and Knee Joint—A Retrospective Analysis of a Certified Arthroplasty Centre of Excellence

Abstract: The treatment of periprosthetic joint infections (PJI), and especially of re-infections, poses a highly complex problem in orthopaedic surgery. While fungal infections are rare, they present a special challenge. The therapy is often protracted and based on limited evidence. A total of 510 hip and knee revision surgeries were analysed for the occurrence of bacterial and fungal PJI. In patients with PJI, the duration of the hospital stay and the incidence of disarticulation of the infected joint were recorded. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…A total of 63 studies on fungal PJI were found. A total of 372 fungal PJI cases were retrieved, most of which were collected from case reports [12,14,, small case series [15,[63][64][65][66][67][68][69][70][71], and only a few from cohort studies with larger samples [3][4][5]8,11,[72][73][74][75][76] (Table 1) Two studies reported an incidence of fungal PJI of 1.9% [8] and 12.4% [73] in the whole PJI cohort.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 63 studies on fungal PJI were found. A total of 372 fungal PJI cases were retrieved, most of which were collected from case reports [12,14,, small case series [15,[63][64][65][66][67][68][69][70][71], and only a few from cohort studies with larger samples [3][4][5]8,11,[72][73][74][75][76] (Table 1) Two studies reported an incidence of fungal PJI of 1.9% [8] and 12.4% [73] in the whole PJI cohort.…”
Section: Resultsmentioning
confidence: 99%
“…Only a few publications described the detection rate of fungi in PJIs in total, reporting a 0.9–2.0% rate [ 8 , 74 , 81 , 82 , 83 ]. However, Enz et al observed [ 73 ] a much higher incidence of fPJI, detecting a fungus in 12.4% of the whole PJI cohort.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 12 studies comprising 153 cases of Candida PJI were included in the final analysis ( Table 2 ) [ 12 , 21 , 22 , 23 , 24 , 25 , 26 , 32 , 33 , 34 , 35 , 36 ]. The number of hip-to-knee PJI was 86 (54.8%) to 67 (46.2%), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…However, one-stage surgical strategies are also performed with good results in different orthopedic centers [ 21 , 22 ]. Recently, several valuable studies concerning Candida PJIs were published [ 12 , 23 , 24 , 25 , 26 ] but not included in currently available systematic reviews [ 17 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…A possible source could be in the biofilm formed by colonizing bacteria [ 41 ]. The bacterial pathogens detected in the revisions Staphylococcus aureus and Enterococcus faecalis are among the most common pathogens in septic revisions [ 42 ]. Some studies showed that sulfide is an important component of the microbial sulfur cycle and S. aureus can use hydrogen sulfide to protect against cationizing molecules from antibiotics [ 43 , 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%